Current State of Pleural-Directed Adjuncts Against Malignant Pleural Mesothelioma - Choi, Agnes Y.; Singh, Anand; Wang, Danyi; Pittala, Karthik; Hoang, Chuong D. (Frontiers in Oncology, 2022)
Multimodality therapy including surgical resection is the current paradigm in treating malignant pleural mesothelioma (MPM), a thoracic surface cancer without cure. The main limitation of all surgical approaches is the lack of long-term durability because macroscopic complete resection (R1 resection) commonly predisposes to locoregional relapse. Over the years, there have been many studies that describes various intrapleural strategies that aim to extend the effect of surgical resection. The majority of these approaches are intraoperative adjuvants. Broadly, there are three therapeutic classes that employ diverse agents. The most common, widely used group of adjuvants are comprised of direct therapeutics such as intracavitary chemotherapy (± hyperthermia). By comparison, the least commonly employed intrathoracic adjuvant is the class comprised of drug-device combinations like photodynamic therapy (PDT). But the most rapidly evolving (new) class with much potential for improved efficacy are therapeutics delivered by specialized drug vehicles such as a fibrin gel containing cisplatin. This review provides an updated perspective on pleural-directed adjuncts in the management of MPM as well as highlighting the most promising near-term technology breakthroughs.